Cancer morbidity and mortality trends in Trinidad and Tobago (2008-2018) - Chavin D. Gopaul; Aruna Singh; Akil Williams; Dale Ventour; Davlin Thomas (BMC, 2023)
Abstract Purpose Cancer is a leading cause of death in the Caribbean, and the Republic of Trinidad and Tobago is no exception. Evidence suggests that cancer incidence and mortality may vary based on demographic factors across the different cancer types. This study aimed to investigate the incidence and mortality trends associated with cancer cases in Trinidad and Tobago for the period 2008-2018, across different age groups, gender, and ethnicity. Methods Data on 15,029 incident cancer cases were reported to the Dr. Elizabeth Quamina Cancer Registry between 2008 and 2018. The retrospective data were analyzed by sex, ancestry, and age, and were reported using Trinidad and Tobago population statistics for the period 2008-2018. Results The incidence of prostate and breast cancers was high among males and females, respectively. Among males, the highest cancer mortality was associated with prostate, lung, colon, blood, and pancreatic cancers, respectively. Among females, the highest cancer mortality was associated with breast, ovary, colon, blood, and pancreatic cancers. The frequency of occurrence of the top five cancer sites was the highest among Afro-Trinidadians followed by Indo-Trinidadians. Most females diagnosed with breast cancer were at a localized stage, while most males diagnosed with breast cancer were at a distant or regional stage. Most individuals diagnosed with blood cancer were at a distant stage. For lung and colon cancer, the stage of diagnosis for most males and females was either distant or unknown. Majority of males are diagnosed with prostate cancer at an unknown stage. Conclusions The findings indicate highest cancer incidence and mortality occur among Afro-Trinidadians. The stage at diagnosis varies across cancer types and gender.